1975
DOI: 10.1111/j.1360-0443.1975.tb01340.x
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Chlormethiazole and Chlordiazepoxide in the Treatment of the Acute Withdrawal Phase of Alcoholism

Abstract: In 1959 (Browne et al.) we published a regime for the treatment of the acute withdrawal phase of alcoholism developed at St. John of God Hospital, and employed in over 300 cases. We had been struck by the vagueness of advice about management of this phase in standard textbooks and by the pre-occupation with individual drugs in reports in the literature. We emphasised the importance of a standardized but flexible approach and used promazine and pentobarbitone as the basic drugs. Over the years as various other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…Chlormethiazole, which is derived from the thiazole moiety of thiamine, possesses sedative, hypnotic, anxiolytic and anticonvulsant properties (1)(2)(3). Chlormethiazole is widely used in some European countries for the treatment of ethanol withdrawal states including delirium tremens (4)(5)(6)(7)(8)(9). It is also widely used clinically as an anticonvulsant in different types of convulsive states.…”
mentioning
confidence: 99%
“…Chlormethiazole, which is derived from the thiazole moiety of thiamine, possesses sedative, hypnotic, anxiolytic and anticonvulsant properties (1)(2)(3). Chlormethiazole is widely used in some European countries for the treatment of ethanol withdrawal states including delirium tremens (4)(5)(6)(7)(8)(9). It is also widely used clinically as an anticonvulsant in different types of convulsive states.…”
mentioning
confidence: 99%
“…Bonnet et al [38] and LaPierre et al [39] found clomethiazole and clonazepam/chlordiazepoxide to be equally effective and tolerable. Compared to chlordiazepoxide, McGrath [40] revealed a tendency of better symptom and delirium control using clomethiazole, while Burroughs et al [34] saw clomethiazole as the more flexibly usable drug. In the most recent study, Millas et al [41] compared oxazepam and clomethiazole.…”
Section: Introductionmentioning
confidence: 99%
“…Presenta, sin embargo, tres serios riesgos: depresión respiratoria, hipersecreción bronquial y riesgo de rápi-da adicción, por lo que no debería utilizarse más que en medio hospitalario. Las benzodiacepinas son una alternativa válida y, en algunos casos, necesaria al clometiazol, aunque su eficacia, especialmente en el tratamiento del delirium tremens, sea inferior (54) . Los principios activos más empleados son diazepam, clordiazepóxido y clorazepato dipotásico.…”
Section: Tratamiento Farmacológico Del Síndrome De Abstinencia Alcohóunclassified